Building Lasting Relationships: CRM Strategies and Customer Loyalty Maxim - Syoftika, Rehan Tri; Rahmiati, Rahmiati (Journal of Management and Administration Provision, 2025)
The digital transportation industry faces fierce competition which requires strategies to maintain customer satisfaction and loyalty as is the case with Maxim transportation services. This study identifies the role of customer relationship management mediated by satisfaction on customer loyalty. This research is quantitative research involving 385 respondents with survey research data collection methods. This research adopts research instruments from previous researchers from reputable journals with Likert scale design instruments. The results of this study reveal that CRM and satisfaction are important aspects in creating loyalty for customers. Satisfaction in this case has shown a partial mediating role, this reveals that CRM will be able to create loyalty whether there is a satisfaction value felt by customers or not.  This research recommends that developing Maxim's customer loyalty in Padang City requires a comprehensive CRM strategy. The implementation of this strategy includes Personalization of services through data-based recommendations, Integration of direct communication channels, Improvement of application facilities, such as rating features and digital payments and Management of customer complaints through a clear evaluation system.